Management of ovulation induction and intrauterine insemination in infertile patients with hypogonadotropic hypogonadism - Kıyak, Hüseyin; Bulut, Berk; Karacan, Tolga; Özyürek, Eser; Gedikbaşı, Ali; Api, Murat (Elsevier, 2019)
Aim: To investigate the effectiveness of ovulation induction and intrauterine insemination (OI + IUI) in female patients with hypogonadotropic hypogonadism (HH), and to compare the outcomes of different stimulation protocols and cycle characteristics. Material and methods: The outcomes of OI + IUI treatments in patients with HH diagnosed between 2010 and 2018 were retrospectively evaluated. Cycles using recombinant (rec) luteinizing hormone (LH) or human menopausal gonadotropin (hMG) as LH sources were compared with each other. The cycle characteristics and pregnancy rates of the first cycles were compared with those of the second cycles in patients who underwent 2 or more cycles. Results: Of 104 patients diagnosed with World Health Organization type 1 anovulation, 99 were treated with hMG or rec LH + rec follicle-stimulating hormone (FSH) in a total of 220 cycles. The mean age of the study patients was 27.8 +/- 4.6 years (range, 19-39 years). Rec FSH + rec LH was given in 37 cycles, and hMG was used in 183 cycles. The hormone values were as follows: FSH, 1.4 +/- 1.6 mIU/mL; LH, 0.7 +/- 1.2 mIU/mL; oestradiol, 13 (15.8 +/- 12.0) pg/mL; and anti-Mullerian hormone, 2.1 (2.6 +/- 1.2) ng/mL. A dominant follicle was observed in 85.7% of the first cycles and in 86.2% of the second cycles. The treatment lasted 17.2 +/- 5.0 and 15.5 +/- 3.8 days until the human chorionic gonadotropin (hCG) administration day in the first and second cycles, respectively, and the difference was statistically significant (p < 0.05). The cycle cancellation rate was 8.1% (n = 3) in cycles done using rec gonadotropins and 29% (n = 53) in patients stimulated with hMG, and the difference was statistically significant (p < 0.05). The pregnancy rates were 12.7% and 28.3% per cycle and per patient, respectively. The pregnancy rate in hCG-triggered patients (successful stimulation) was 17.1% per cycle in all patients. Conclusion: OI with gonadotropins and IUI is a safe, efficient, and relatively cost-effective treatment option in patients with HH, yielding reasonable pregnancy rates per cycle and per patient. The use of rec FSH + rec LH facilitates cycle management but does not positively contribute to pregnancy rates and is more expensive than some other feasible options. (C) 2019 Elsevier Masson SAS. All rights reserved.
Keywords: Hypogonadotropic Hypogonadism; Intrauterine İnsemination; Pregnancy Rate; Gonadotropin Stimulation